Characteristics of sisal-epoxy composite boards with sodium chloride-treated fibers at different treatment temperatures - Setyayunita, Tamaryska; Suryanto, Heru; Aminnudin, Aminnudin; Osman, Azlin Fazlina; Yanuhar, Uun (Universitas Negeri Padang, 2025)
The growing environmental concerns associated with synthetic fibers have led to the increased adoption of bio-fibers as reinforcements in polymer composites. Sodium chloride (NaCl) is explored as a fiber treatment agent to enhance the adhesion between fibers and the matrix. The study aims to evaluate the effects of NaCl treatment on the characteristics of sisal fiber-epoxy composite boards. A completely randomized design was applied with three factors: treatment temperature (25 °C and 100 °C), NaCl concentration (1, 3, and 5 wt%), and composite board density (0.40, 0.60, and 0.80 g/cm³). Sisal fibers were soaked in NaCl solutions for one hour, rinsed, dried, and manually blended with epoxy at a ratio of 80:20 wt%. Composite board properties were observed according to the standards of JIS-A-5908, Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). Results indicated that increasing the NaCl concentration and treatment temperature significantly improved the properties of the composite board. The optimal parameters (5wt% NaCl, 100 °C, 0.80g/cm³) yielded a modulus of elasticity of 4.59±0.26 GPa, modulus of rupture of 18.88±0.03 MPa, and internal bond strength of 3.92±0.18 MPa, representing increases of 200.32%, 130.65%, and 218.70%, respectively. Thickness swelling decreased to 2.13±0.43% (48.14%) and water absorption to 8.95±0.05% (32.25%). These findings confirm that NaCl treatment is an eco-friendly method to enhance the mechanical strength and moisture resistance of biofiber composites. It also supports the development of high-performance composite boards.